The impact of alliance justice capability on the performance of strategic alliances in the Indian IT sector: the mediating role of inter-firm commitment - Mayank Dhaundiyal; Joseph Coughlan (Cogent Business & Management, 2020)
This paper conceptualizes and operationalizes alliance justice capability (AJC) as a second order firm-level capability consisting of three distinct yet related first-order firm level skills which foster procedural justice (PJ), distributive justice (DJ) and interactional justice (IJ) in the relationship between alliance partners. The paper then goes on to test how AJC affects alliance performance, mediated by inter-firm affective commitment and calculative commitment. This model is tested via a survey that yielded 154 complete responses from alliance managers in the Indian Information Technology sector. The data was analysed with structural equation modelling using Mplus. Research findings partially validate the theoretical model put forward in this paper demonstrating the mediating role of affective commitment in the relationship between AJC and alliance performance.
Keywords: 650; organizational justice; strategic alliance; distributive justice; procedural justice; interactional justice; affective commitment; calculative commitment